Alat Penggorengan Abon Ikan Berpenggerak Motor Listrik 200 Watt - Yohanes T. Luluk; Ishak S. Limbong; Jack C.A. Pah; Murni Pallawagau (Universitas Nusa Cendana, 2025)
Fisheries play a crucial role in the Indonesian economy, particularly for fishermen and coastal communities. However, fishery products such as fish floss have problems in the frying process, which requires continuous human power to stir. This research aims to design and develop a fish floss frying device powered by an electric motor with a driving power of 200 W. This tool is expected to facilitate the fish floss frying process, reduce the energy expended by the fish floss maker, and increase the efficiency of the production process. This research uses data collection methods, tool design, and tool testing. Autodesk Inventor software was used in the design stage to design the tool frame, stirrer, and pan holder. This tool includes an electric motor, gearbox, pulley, V-belt, and frying pan. Then, the tool was made using a hollow iron box, a stainless-steel pipe, and wood. This research yields a fish floss fryer equipped with an electric motor, capable of frying fish floss with a capacity of up to 3 kg. This tool can help ease the work of frying fish floss, save labour, and increase production efficiency. With a driving power of 200 W, this tool can produce good-quality fish floss